2013
DOI: 10.17795/jhealthscope-11414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Educating Self-Care Behaviors to Patients With Heart Failure in Hospitals of Zahedan

Abstract: Background: Heart failure is a chronic disease in the elderly. Self-care education has a significant role in preventing the disease, its progress, and complications. Objectives: The present study aimed to assess the effect of training on self-care behaviors among patients with heart failure in hospitals of Zahedan City in 2012. Materials and Methods:The present study had a quasi-experimental interventional design with control group, and was conducted in CCU and post-CCU wards in hospitals affiliated to Zahedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
(34 reference statements)
4
11
1
1
Order By: Relevance
“…So that more than half of the patients answered these questions negativity. In a study conducted by Sajedi in Hamedan, it was reported that patients were not highly aware of their medicine and food diet (11), which showed a result not in line with the findings of the current study. However, in the study of Sajedi, it was found that more than 90% of the patients reported that they were taking their medicines as prescribed, and 70% of them mentioned that they were following a low-salt diet.…”
Section: Discussioncontrasting
confidence: 97%
“…So that more than half of the patients answered these questions negativity. In a study conducted by Sajedi in Hamedan, it was reported that patients were not highly aware of their medicine and food diet (11), which showed a result not in line with the findings of the current study. However, in the study of Sajedi, it was found that more than 90% of the patients reported that they were taking their medicines as prescribed, and 70% of them mentioned that they were following a low-salt diet.…”
Section: Discussioncontrasting
confidence: 97%
“…Finally, the results demonstrated that the change in the mean score for selfcare behaviors was statistically significant in the intervention group (P < 0.001) but not in the control group. These findings are in accordance with those of studies performed previously (8,27,(41)(42)(43).…”
Section: Discussionsupporting
confidence: 94%
“…Cardiovascular diseases are the first cause of death in Iran, and as the most important challenge to the health care system of the country, it accounts for more than one-third of all deaths (39%). Road accidents and cancer are the second and third leading causes of death in Iran (Ahmadi et al 2014) with so many economic burden and social consequences (Seraji et al 2013).…”
Section: Introductionmentioning
confidence: 99%